Electoral Politics in Zimbabwe, Vol II
XXV, 433 p. 11 illus., 8 illus. in color.
Keywords: "If Zimbabwe won political independence in 1980 and reclaimed land in 2000, it is yet to win democracy. Elections in Zimbabwe remain not only a site of violence, but participation of women is limited too. Media is instrumentalised just as traditional leaders are patronised for political ends. This collection of well-researched essays on the subject of elections is most welcomed and makes an indispensable addition to the understanding of problematic political culture in Zimbabwe." –Sabelo J. Ndlovu-Gatsheni, Professor/Chair of Epistemologies of the Global South & Vice-Dean for Research of the Africa Multiple Cluster of Excellence, University of Bayreuth, Germany. Volume two of Electoral Politics in Zimbabwe: The 2023 Election and Beyond argues that research into Zimbabwe’s politics is multifaceted and topical, particularly because for more than two decades now, this Southern African state has been dogged by multiple problemsincluding hyperinflation, drought, escalating poverty levels, extremely high unemployment rates and political instabilities. The volume’s overall goal is to ignite intellectual discussions and practical action towards turning the political wheels that have been in place for decades. The first segment examines the interface between gender and electoral politics in Zimbabwe. The second part discusses the role of the media in Zimbabwe’s electoral politics. The third section reflects on the role of traditional leaders and religious discourses in Zimbabwe’s electoral politics. The book will be a key resource to colleges, universities and organisations in Zimbabwe, the Southern Africa region and even beyond. Esther Mavengano is Lecturer in the Faculty of Arts at Great Zimbabwe University in Masvingo, Zimbabwe. She is also Research Fellow at the Research Institute for Theology and Religion, UNISA, South Africa, and Alexandervon Humboldt Postdoctoral Research Fellow at the Institute of English and American Studies, Technischen Universität Dresden, Germany. Sophia Chirongoma is Senior Lecturer in the Religious Studies Department at Midlands State University, Zimbabwe. She is also Academic Associate/Research Fellow at the Research Institute for Theology and Religion at the University of South Africa. .